2005
DOI: 10.1590/s0103-90162005000300013
|View full text |Cite
|
Sign up to set email alerts
|

Plant bioassays to assess toxicity of textile sludge compost

Abstract: Composting of industrial wastes is increasing because of recycling requirements set on organic wastes. The evaluation of toxicity of these wastes by biological testing is therefore extremely important for screening the suitability of waste for land application. The toxicity of a textile sludge compost was investigated using seed germination and plant growth bioassays using soybean and wheat. Compost samples were mixed with water (seed germination bioassay) or nutrient solution (plant growth bioassay) at concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 20 publications
2
46
0
9
Order By: Relevance
“…Morera et al (2002) also reported a reduction in the HM toxicity due to adsorption of HMs by additional sources of OM and humic substances in sludge. Araùjo & Monteiro (2005) showed that seed coats constitute a barrier between the embryo and its immediate environment. According to these authors, the metals occurring in the substrate could be adsorbed by the seed coat, which would thus not affect the growth of the embryonic root.…”
Section: Discussionmentioning
confidence: 99%
“…Morera et al (2002) also reported a reduction in the HM toxicity due to adsorption of HMs by additional sources of OM and humic substances in sludge. Araùjo & Monteiro (2005) showed that seed coats constitute a barrier between the embryo and its immediate environment. According to these authors, the metals occurring in the substrate could be adsorbed by the seed coat, which would thus not affect the growth of the embryonic root.…”
Section: Discussionmentioning
confidence: 99%
“…They found that roots were inhibited by 70%, while shoots were reduced only by 50% in the presence of Zn.The inhibition of roots and shoots elongation caused by heavy metals can be due to their influence on cell division (Davies et al, 1991;Hargemeyer, Breckle, 1996), or their effect on cell wall elasticity and metabolic activities (Naseer et al, 2001). As we know, roots are the first part of the plant that comes in touch with contamination, they are more sensitive to toxicity by metals than shoots (Araujo, Monteiro, 2005;Shah et al, 2010;Yang et al, 2010;Yusuf et al, 2011). This sensibility reduced per consequence of the root/shoot ratio.…”
Section: Discussionmentioning
confidence: 99%
“…According to Seregin and Kozhevnikova, (2005), seed germination is the most resistant process to heavy metals; this resistance was due to weak penetration through the seed coat of heavy metals. The seed coat can be a barrier between the embryo and the environment in the immediate vecinity (Araùjo and Monteiro, 2005); it protects the embryo against the heavy metals toxicity, isolated embryo were more sensitive to heavy metals than seeds intact (Li et al, 2005).…”
Section: Effect Of Zinc On the Germinationmentioning
confidence: 99%